1994
DOI: 10.2337/diacare.17.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Alrial Natriuretic Factor in Hypertensive and Normotensive Diabetic Patients

Abstract: These findings indicate that circulating ANF levels are markedly elevated in type II diabetic patients affected by essential hypertension. On the contrary, plasma ANF levels are in the range of normality in normotensive type I and type II diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Elevation of plasma ANP concentrations by intravenous ANP infusions has been shown to increase UAER in Type 1 DM patients with established microalbuminuria[8–9], but this is the first demonstration that ANP can increase UAER in normoalbuminuric patients. This albuminuric effect of ANP may be of pathological significance as plasma concentrations of ANP are elevated in clinical situations such as hypertension and poor glycaemic control, which predict the future development of nephropathy in diabetes mellitus[2,3–6]. The demonstration that ANP can increase albuminuria in normoalbuminuric patients supports this hypothesis and there is evidence from animal data that ANP may be important in the early development of abnormal haemodynamics and altered albumin excretion.…”
Section: Discussionmentioning
confidence: 98%
“…Elevation of plasma ANP concentrations by intravenous ANP infusions has been shown to increase UAER in Type 1 DM patients with established microalbuminuria[8–9], but this is the first demonstration that ANP can increase UAER in normoalbuminuric patients. This albuminuric effect of ANP may be of pathological significance as plasma concentrations of ANP are elevated in clinical situations such as hypertension and poor glycaemic control, which predict the future development of nephropathy in diabetes mellitus[2,3–6]. The demonstration that ANP can increase albuminuria in normoalbuminuric patients supports this hypothesis and there is evidence from animal data that ANP may be important in the early development of abnormal haemodynamics and altered albumin excretion.…”
Section: Discussionmentioning
confidence: 98%
“…BNP secretion from cardiac ventricles is stimulated by volume or pressure overload, and its vasodilating effect is mediated by A-type guanylate cyclase-coupled receptor (NPR-A) (1,2). The plasma levels of the atrial natriuretic peptide (ANP) were previously reported to increase in normotensive diabetic patients with microalbuminuria (3)(4)(5)(6). The secretion of ANP is stimulated by increased atrial pressure associated with volume or pressure overload (1,2).…”
mentioning
confidence: 98%
“…Impaired left ventricular function, even if clinically asymptomatic, goes along with elevated circulating ANP plasma concentrations [21] -although resting ANP plasma concentrations in DM patients without hypertension are in the normal range [22], the increase in plasma ANP concentrations during moderate exercise is greater in diabetic patients than in controls, suggesting reduced left ventricular diastolic function and increased arterial stretch [23].…”
Section: Discussionmentioning
confidence: 99%